IEC 61499 function blocks for embedded and distributed control systems design - Vyatkin, Valeriy (ISA, 2012)
IEC 61499 is the standard for distributed control systems that follows on from the IEC 61131 standard for programmable logic controllers (PLC). This book is a practical guide for component-based development of distributed embedded and control systems as proposed by this international standard. Each chapter is designed as an independent study unit, making the book ideal for use in university courses, industrial training, or self-study. Working knowledge of the IEC 61499 standard can be achieved in approximately 10 to 15 learning hours. For the control, automation, or software engineer and the embedded systems developer, this book provides concrete directions on how to specify and implement a distributed system according to the IEC 61499 standard and how to create an IEC 61499-compliant control device. The text also sheds some light on the broader embedded systems arena since the IEC 61499 standard provides the higher level (yet executable!) abstraction appropriate for model-based engineering of distributed embedded systems.
Keywords: Programmable controllers -- Charts, diagrams, etc. -- Standards.; Automatic control -- Charts, diagrams, etc. -- Standards.; Distributed parameter systems -- Standards.; Embedded computer systems -- Standards.; elektronické knihy; electronic books